Effect of increasing the mass of the ball on power output during the overarm throw in professional male handball players - Gutiérrez-Dávila, M.; Sánchez-Sánchez, F.; Gutiérrez-Cruz, C.; Garcia-Ramos, A. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
This study aimed to determine the effect of increasing the mass of the official handball ball on horizontal force, velocity, and power outputs. Twelve male handball players from the Spanish Asobal Handball League performed overarm throws with four balls: official (0.460 kg), d15% (0.529 kg), d45% (0.667 kg), and d75% (0.805 kg). The throws were filmed with two cameras temporally synchronized at 250 Hz and digitized at 125 Hz, making possible to obtain the spatial coordinates of a model composed by six body markers plus the geometric center of the ball. Incrementing the mass of the ball produced a progressive reduction in velocity and increase in force (p < 0.001). The power tended to increase with the increment of the mass, but significant differences were only reached for the heaviest condition (d75%) and it was linked to changes in the application of force with respect to time. The maximum values of force, velocity and power with respect to the release of the ball, were delayed with the increment of the mass (p < 0.001). These results evidence that the power applied to the ball can only be increased when heavy balls, which modify the structure of the throw, are used.